Strategi Pengembangan Produk Piring Biodegradable melalui Analisis SWOT pada Piring Daun Jati JEcoware - Bacellia Yolanda Bomboa; Fashya Khoerunnisa; Awin Mulyati (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
JEcoware is an eco-friendly innovation in the form of biodegradable plates made from teak leaves and recycled cardboard. This product was developed to address the growing problem of plastic waste, particularly in the household and food industry sectors. This study employs a SWOT analysis to identify the strengths, weaknesses, opportunities, and threats of the product in the market. The results indicate that the product has great potential in the eco-friendly market, despite challenges such as product durability and low public awareness. With well-directed strategies, such as technological innovation and collaboration with local farmers, JEcoware has the potential to enhance competitiveness and expand its market to the international level.